THE FIRST EXPERIENCE OF USING ANTI-VEGF THERAPY PRIOR TO CATARACT SURGERY IN PATIENTS WITH DIABETIC MACULAR EDEMA - N. A. Malysheva (Российский офтальмологический журнал)
Purpose: assess the effectiveness of anti-VEGF therapy given prior to cataract phacoemulsification in preventing the progression of diabetic macular edema. Material and methods. The retrospective study included 15 patients (15 eyes) with type 2 diabetes who underwent cataract surgery. Group 1 included 8 patients who received anti-VEGF therapy before surgical treatment. The last injection of aflibercept was performed no earlier than 2 weeks before the surgery, regardless of central retinal thickness (CRT) increase. Group 2 included 7 patients who did not receive anti-VEGF therapy before surgery. All patients received standard presurgical preparation. The changes in visual acuity and CRT were assessed on days 5 and 14 after cataract extraction. Results. On day 5, the mean increase of visual acuity was 0.34 ± 0.05 in Group 1 and 0.275 ± 0.07 in Group 2. The mean CRT decrease was 47 μm in group 1, while group 2 showed a mean CRT increase of 135 μm. On day 14, the visual acuity was 0.49 ± 0.1 higher than the initial value in group 1, whilst in group 2 it was 0.21 ± 0.07 lower than on day 5. The mean CRT decrease was 80 μm in group 1, while group 2 revealed a 165 μm increase of CRT. Conclusion. Anti-VEGF therapy prior to cataract surgery of patients with diabetic macular edema should become mandatory if CRT has increased, regardless of visual acuity, since visual acuity measurement is impossible due to cloudy lens environments. The use of aflibercept in patients with clinically insignificant diabetic macular edema 1 month before the planned cataract surgery ensures a positive result of visual acuity increase and improvement of anatomical parameters. For citation: Malysheva N.A. The first experience of using anti-VEGF therapy prior to cataract surgery in patients with diabetic macular edema. Russian ophthalmological journal. 2018; 11 (3): 55-61 (In Russian). doi: 10.21516/2072-0076-2018-11-3-55-61